The Effectiveness of the Cognitive Development Strategy KWLH in Developing Physical Concepts among Second Grade Students in Iraq - Aldulaimi, Hisham; Almomani, Jehad (Dirasat: Educational Sciences, 2021)
This study aims at identifying the effectiveness of the KWLH strategy for monitoring the development of physical concepts among second grade students in Iraq and their attitudes towards learning physics. The researchers followed a semi-experimental approach. The sample of the study consisted of (60) middle second grade students for the academic year 2019/2020 in Abi Dhar Al-Ghaffari school for boys in Anbar Governorate. They were divided into two groups: one was randomly chosen to be an experimental group that was taught using a cognitive development monitoring strategy and the other was a control group that was taught in the usual way. To achieve the goal of the study, the researchers prepared an achievement test for the physical concepts and a scale of attitudes toward learning physics; their validity and reliability were verified before being distributed to the study sample. The results of the study showed that there is a statistically significant difference between the arithmetic averages of the performance of the sample members on the achievement test and the scale of attitudes attributed to the method of teaching in favor of the members of the experimental group who have been taught using the strategy of monitoring cognitive development. Based on these results, the study recommends the necessity of paying attention to the strategy of monitoring cognitive development and preparing training programs for teachers of physics to employ this strategy in teaching.